The analysis on teaching skills and learning effectiveness of internship students - Abdul Rachman Syam Tuasikal; Setiyo Hartoto; Bayu Budi Prakoso; Dwi Cahyo Kartiko; Agus Hariyanto (Jurnal Cakrawala Pendidikan, 2021)
The effectiveness of implementing Pengenalan Lapangan Persekolahan, a new program of introduction to teaching internship, for PE students, is still questionable, starting from its impact on teaching skills, learning effectiveness, and students' teaching load. Meanwhile, this point is significant in Kurikulum Merdeka Belajar Kampus Merdeka (MBKM). For this reason, this analytic study will criticize MBKM by providing evidence of the effectiveness of existing internships in the form of teaching skills, learning effectiveness, and students' teaching load. A total of 32 students were selected using consecutive sampling. Teaching skills were measured by observing 12 indicators and learning effectiveness was measured using Formative Class Evaluation (FCE) instrument. Anova Repeated Measure was used to analyse the data. The results show that the new program of introduction to teaching internship is not practical, proved by the progressive improvement of teaching skills followed by the ineffectiveness of the learning process. Students feel they have an overload teaching schedule, so that self-development activities are minimal, even though the tutor teachers have guided optimally. It can be concluded that the new program of introduction to teaching internship is less effective because of the overload teaching schedule in such limited time. It is then expected that the longer internship duration would enrich students' experiences under supervision and more comprehensive teaching load regulation.